Review of digital holographic microscopy for three-dimensional profiling and tracking - Yu, Xiao; Hong, Jisoo; Liu, Changgeng; Kim, Myung K (Optical engineering, 2014)
Digital holographic microscopy (DHM) is a potent tool to perform three-dimensional imaging and tracking. We present a review of the state-of-the-art of DHM for three-dimensional profiling and tracking with emphasis on DHM techniques, reconstruction criteria for three-dimensional profiling and tracking, and their applications in various branches of science, including biomedical microscopy, particle imaging velocimetry, micrometrology, and holographic tomography, to name but a few. First, several representative DHM configurations are summarized and brief descriptions of DHM processes are given. Then we describe and compare the reconstruction criteria to obtain three-dimensional profiles and four-dimensional trajectories of objects. Details of the simulated and experimental evidences of DHM techniques and related reconstruction algorithms on particles, biological cells, fibers, etc., with different shapes, sizes, and conditions are also provided. The review concludes with a summary of techniques and applications of three-dimensional imaging and four-dimensional tracking by DHM.